Percival Lowell as a researcher of Japanese culture - D.E. Martynov; Yu.A. Martynova; R.R. Mukhametzanov (Ученые записки Казанского университета: Серия Гуманитарные науки, 2017)
This paper analyzes Percival Lowell's (1855–1916) views on the characteristics of Japanese culture. During the period of 1882–1893, he made three scientific trips to Japan and Korea, which were the result of four books and several papers in periodicals. In his works, P. Lowell introduced a holistic image of the Japanese traditional culture, which he identified with the Far Eastern civilization as a whole system. He was a great connoisseur of Japanese landscape art and ikebana. The value of his work is that P. Lowell performed a comparative research of the highly developed traditional culture with the cultural type of modernity. He raised questions of personal identity in the traditional culture. Books and articles written by P. Lowell remain important as the primary sources for Japanese art and Shinto rituals. We have used the comparative and historical-typological methods to analyze P. Lowell's main works: “Chosön, the Land of the Morning Calm: A Sketch of Korea”; “The Soul of the Far East”; and “Occult Japan: Or, the Way of the Gods”. It is obvious from these works that P. Lowell considered Japan as a “mirror world” of the West and studied it through the prism of social Darwinism. He was the first to develop the mechanisms for investigating Japan. One of the methods was comparison of the national psychologies of the Japanese and Europeans, which was more comprehensive than M. Weber's ideal types. He pioneered in the research on the mental characteristics of traditional cultures in field conditions by focusing on esoteric (trance-like) rituals. P. Lowell raised questions of personal identity in the society dominated by archaic forms of living and concluded that it is influenced greatly by external mechanisms, mostly family, suppressing individuality. P. Lowell believed that the westernization of Japan is impossible, because the Japanese mind is unable to learn the achievements of Western science. The consequences of these views were that P. Lowell's studies on Japan were never reprinted until 2006.